2010
DOI: 10.4103/0974-1208.74155
|View full text |Cite
|
Sign up to set email alerts
|

Effect of body mass index on in vitro fertilization outcomes in women

Abstract: BACKGROUND:Obesity has become a major health problem across the world. In women, it is known to cause anovulation, subfecundity, increased risk of fetal anomalies and miscarriage rates. However, in women going for assisted reproduction the effects of obesity on egg quality, embryo quality, clinical pregnancy, live birth rates are controversial.OBJECTIVES:To assess the effect of women’s body mass index (BMI) on the reproductive outcome of non donor In vitro fertilization (IVF)/Intracytoplasmic sperm injection (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 10 publications
3
27
0
3
Order By: Relevance
“…In Erel et al, 2009 a literature review was performed difference between patients with different BMI. Zander -Fox et al, 2012, Singh et al, 2012, Vilarino et al, 2011, Bellver et al, 2010and Sathya et al, 2010 have not Sneed et al, 2008, showed that the interaction between however, BMI alone had no apparent effect. This had a greater impact on patients under 36 years, because in older women age became the most important factor.…”
Section: Number Of Oocytes Retrievedmentioning
confidence: 99%
See 1 more Smart Citation
“…In Erel et al, 2009 a literature review was performed difference between patients with different BMI. Zander -Fox et al, 2012, Singh et al, 2012, Vilarino et al, 2011, Bellver et al, 2010and Sathya et al, 2010 have not Sneed et al, 2008, showed that the interaction between however, BMI alone had no apparent effect. This had a greater impact on patients under 36 years, because in older women age became the most important factor.…”
Section: Number Of Oocytes Retrievedmentioning
confidence: 99%
“…One was the study of Veleva et al (2008) , which showed that the BMI graph curve that represents how BMI affects the miscarriage rate is U-shaped, meaning that patients of low weight also has their increased risk, independent of patient age ( Figure 3 ). Moreover, the revision of Rittenberg et al, 2011 revealed increased miscarriage rate in 14 studies (RR 1.36, 95 % CI 1.13 to 1.64, p et al, 2010, despite the rate being increased, this increase was not significant, as in Vilarino et al, 2011, Zhang et al, 2010and Sathya et al .,2010. Sneed et al, 2008 showed that miscarriage rate is not directly affected by BMI, but by the interaction between BMI and age, with age the main determining factor.…”
Section: Miscarriage Ratementioning
confidence: 99%
“…Although studies demonstrated that no change of gonadotropin treatment was implied in different BMI [50,51], there are several studies have argued that higher dosage of gonadotropin and longer treatment duration exhibited in patients with BMI more than 25 kg/m 2 [52,53]. Interestingly, in our results, no significant difference on clinical pregnancy rate was observed by the change of BMI in non-PCOS patients whereas overweight and obese women with PCOS showed significant decrease in clinical pregnancy rate, suggesting BMI may affect the outcome of IVF/ICSI only in PCOS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Normal BMI versus BMI 25-29.9 kg/m 2 : pooled analysis from five studies (Dechaud et al, 2006;Esinler et al, 2008;Bellver et al, 2010;Sathya et al, 2010;Zhang et al, 2010) showed a higher dose of gonadotrophin stimulation in women with BMI 25-29.9 kg/m 2 compared with women with normal BMI (WMD 137.92,, P = 0.005). There was a significant heterogeneity between the included studies (I 2 = 61.2%).…”
Section: Dose Of Gonadotrophin Stimulationmentioning
confidence: 99%